World Income Inequality Databases: An assessment of WIID and SWIID - Stephen P. Jenkins (University of Essex, Institute for Social and Economic Research (ISER), 2014)
This article assesses two secondary data compilations about income inequality - the World Income Inequality Database (WIIDv2c), and the Standardized World Income Inequality Database (SWIIDv4.0) which is based on WIID but with all observations multiply-imputed. WIID and SWIID are convenient and accessible sources for researchers seeking cross-national data with global coverage for relatively long time periods. Against these benefits must be set costs arising from lack of data comparability and quality and also, in the case of SWIID, questions about its imputation model. WIID and SWIID users need to recognize this benefit-cost trade-off and ensure their substantive conclusions are robust to potential data problems. I provide detailed description of the nature and contents of both sources plus illustrative regression analysis. From a data issues perspective, I recommend WIID over SWIID, though my support for use of WIID is conditional.
Keywords: C81; C82; D31; 330; global inequality; inequality; Gini; imputation; WIID; SWIID